2009
DOI: 10.1080/00050060903262387
|View full text |Cite
|
Sign up to set email alerts
|

Mental health help-seeking and refugee adolescents: Qualitative findings from a mixed-methods investigation

Abstract: There is general agreement in Australia and other Western resettlement countries that many refugee adolescents with social, behavioural, and mental health problems are not accessing mental health care. There is, however, a paucity of research on refugee adolescent mental health service utilisation and help-seeking. Most research to date has centred on adolescents in the general population, and even then is still very limited. This paper presents the findings of 13 focus groups held with 85 refugee adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
129
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 22 publications
12
129
1
Order By: Relevance
“…Leavey, Guvenir, Haase-Casanovas and Dein (2007) suggested families should be engaged because they play a pivotal role in the nature and timing of help-seeking. In contrast, de Anstiss and Ziaian (2010) highlighted that young people may not feel comfortable discussing personal issues with their parents and Ellis and collaborators (2010) found that youth were concerned that telling their parents -who had already many other significant worries associated with war and resettlement -about their problems, would unduly burden them. As suggested by the service providers in this study, best practice may be asking the young person what role they would like their family to play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leavey, Guvenir, Haase-Casanovas and Dein (2007) suggested families should be engaged because they play a pivotal role in the nature and timing of help-seeking. In contrast, de Anstiss and Ziaian (2010) highlighted that young people may not feel comfortable discussing personal issues with their parents and Ellis and collaborators (2010) found that youth were concerned that telling their parents -who had already many other significant worries associated with war and resettlement -about their problems, would unduly burden them. As suggested by the service providers in this study, best practice may be asking the young person what role they would like their family to play.…”
Section: Discussionmentioning
confidence: 99%
“…Participants noted refugee young people (and their families) frequently balance competing settlement priorities, and dealing with clients' immediate needs can provide an entry into a therapeutic relationship. This was suggested as particularly important in the context of mental health being considered a low priority (Behnia, 2003;de Anstiss & Ziaian, 2010;Palmer, 2006). Previous literature supported the concept of taking an advocacy role, addressing also practical concerns, and a holistic approach (Behnia, 2003;Cleveland, Rousseau, & Guzder, 2014;de Anstiss & Ziaian, 2010;Hodes, 2002;McColl & Johnson, 2006;Misra, et al, 2006;Palmer, 2006;Ward & Palmer, 2005;Watters & Ingleby, 2004;Woodland, Burgner, Paxton, & Zwi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers may also be traumatized by violence, injustice, and instability (Klingman, 2006;Saile et al, 2014). Reports of traumatized and emotionally unavailable caregivers are found in studies of war-affected children (Al-Mashat et al, 2006;Almqvist & Brandell-Forsberg, 1997;Anstiss & Ziaian, 2010;Dyregrov et al, 2002;Hadi & Llabre, 1998;Henley & Robinson, 2011;Laor et al, 1997;Paardekooper et al, 1999;Qouta et al, 2003;Saile et al, 2014;Thabet et al, 2008). Various studies have found that there is a higher rate of mental health problems within refugee parent populations as opposed to civilian populations (McFarlane et al, 2011).…”
Section: Bonds and Attachmentmentioning
confidence: 99%
“…However, several other maladaptive responses are potentially linked with safety violations. Psychosomatic complaints (McFarlane et al, 2011;Paardekooper et al, 1999;Sezibera et al, 2009), guilt (Goldstein et al, 1997;McFarlane et al, 2011), neuroticism (Punamäki et al, 2001), underreporting of post-traumatic symptoms due to fear of stigma (Anstiss & Ziaian, 2010;Colucci, Minas, Szwarc, Paxton, & Guerra, 2012;Servan-Schreiber et al, 1998;Thabet & Vostanis, 2000), and developing an external locus of control (Kuterovac-Jagodic, 2003) are also described in groups of children following wartrauma. In total, these maladaptive responses likely contribute to adjustment difficulties for children and adolescents as they seek to begin new lives following war.…”
Section: Maladaptive Responsesmentioning
confidence: 99%
See 1 more Smart Citation